Vascular resistance of carotid and vertebral arteries is associated with retinal microcirculation measured by laser speckle flowgraphy in patients with type 2 diabetes mellitus. (July 2020) - Sawada, Shojiro; Tsuchiya, Satoko; Kodama, Shinjiro; Kurosawa, Satoko; Endo, Akira; Sugawara, Hiroto; Hosaka, Shinichiro; Kawana, Yohei; Asai, Yoichiro; Yamamoto, Junpei; Munakata, Yuichiro; Izumi, Tomohito; et al.
Abstract: Aims: Evaluation of the retinal microcirculation is key to understanding retinal vasculopathies, such as diabetic retinopathy. Laser speckle flowgraphy (LSFG) has recently enabled us to directly evaluate the vascular resistance in both retinal vessels and capillaries, non-invasively. We therefore assessed whether retinal vessel blood flow and/or the capillary microcirculation are associated with blood flow in the cervical arteries in diabetic patients without severe retinopathy. Methods: We enrolled 110 type 2 diabetes patients, with no or mild non-proliferative diabetic retinopathy, in this prospective cross-sectional study. We measured the resistivity indices (RIs) of the retinal vessel and capillaries by LSFG and those of cervical arteries by Doppler ultrasonography, followed by analyzing associations. Results: The RIs of not only the carotid but also vertebral arteries were associated with those of retinal vessel blood flow and the retinal capillary microcirculation. Multiple regression analyses revealed these associations to be independent of other explanatory variables including age and diabetes duration. Conclusions: We obtained novel and direct evidence demonstrating a close association between the retinal microcirculation and cervical artery hemodynamics in diabetic patients. These findings suggest shared mechanisms to underlie micro- and macro-angiopathies. Thus, high vascular resistance of cervical arteries may be a risk of developing retinopathy.